HUBUNGAN DERAJAT TILS INTRATUMORAL DAN STROMAL TERHADAP SUBTIPE TUMOR MUCINOUS OVARIUM DI RSUP H. ADAM MALIK MEDAN: ASSOCIATION BETWEEN INTRATUMORAL AND STROMAL TILS DEGREES AND MUCINOUS OVARIAN TUMOR SUBTYPES AT H. ADAM MALIK GENERAL HOSPITAL MEDAN - Kadri, Sayed Muhammad; Delyuzar; Intan, T. Kemala; Soekimin; Lukito, Joko S; Chrestella, Jessy (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2026)
Mucinous ovarian tumors represent a distinct subtype of epithelial ovarian neoplasms with varying biological behaviors and histopathological features. Tumor-infiltrating lymphocytes (TILs), both intratumoral and stromal, have emerged as prognostic biomarkers in various malignancies, including ovarian cancer. Objective of this study is to analyze the association between intratumoral and stromal TILs degrees with mucinous ovarian tumor subtypes at H. Adam Malik General Hospital, Medan. A cross-sectional analytic study was conducted on 42 formalin-fixed paraffin-embedded tissue samples diagnosed as mucinous ovarian tumors. TILs were assessed on H&E-stained slides using criteria from the International TILs Working Group. Statistical analysis employed Chi-square tests. Results of this study show that high intratumoral TILs were predominantly found in benign mucinous tumors, while low intratumoral TILs were common in malignant cases (p = 0.002). Similarly, high stromal TILs were more frequent in benign subtypes, and low stromal TILs were significantly associated with malignant subtypes (p = 0.000). Conclusion of this study is that there is a significant association between intratumoral and stromal TILs degrees and the histological subtypes of mucinous ovarian tumors. Higher TILs levels are more frequently found in benign tumors, suggesting a potential role as a prognostic indicator. AbstrakTumor ovarium mucinous merupakan salah satu subtipe neoplasma epitel ovarium dengan perilaku biologis dan karakter histopatologi yang bervariasi. Tumor-infiltrating lymphocytes (TILs), baik intratumoral maupun stromal, telah diidentifikasi sebagai biomarker prognostik pada berbagai jenis keganasan, termasuk kanker ovarium. Tujuan penelitian ini adalah untuk mengetahui hubungan antara derajat TILs intratumoral dan stromal dengan subtipe histopatologi tumor mucinous ovarium di RSUP H. Adam Malik Medan. Penelitian analitik potong lintang dilakukan terhadap 42 sampel jaringan tumor mucinous ovarium yang telah difiksasi formalin dan diblok parafin. Penilaian TILs dilakukan pada preparat hematoksilin-eosin (HE) berdasarkan pedoman dari International TILs Working Group. Analisis statistik menggunakan uji Chi-square. Hasil penelitian memperlihatkan bahwa derajat TILs intratumoral tinggi paling banyak ditemukan pada tumor mucinous jinak, sedangkan TILs rendah dominan pada tumor mucinous ganas (p = 0,002). Hal serupa ditemukan pada TILs stromal, di mana TILs tinggi lebih sering pada tumor jinak, dan TILs rendah lebih sering pada subtipe ganas (p = 0,000). Kesimpulan penelitian ini adalah terdapat hubungan bermakna antara derajat TILs intratumoral dan stromal dengan subtipe histopatologi tumor mucinous ovarium. Derajat TILs yang lebih tinggi berhubungan dengan subtipe yang lebih jinak, sehingga berpotensi sebagai indikator prognosis.